Early Infantile Diagnosis of Hereditary Hemorrhagic Telangiectasia Complicated by Child Abuse - Brittany Tang, MD; Stephen Pophal, MD; Madhusudan Ganigara, MD; Brian Funaki, MD; Mckenna Robinette, APRN; Veena Ramaiah, MD; Nancy Ghanayem, MD; Michael C. Hurley, MD; Umesh Dyamenahalli, MD (Elsevier, 2024)
We report a rare case of hereditary hemorrhagic telangiectasia (HHT) in a 4-month-old female infant with findings of child abuse. She presented with poor feeding, vomiting, and irritability after a short fall from the bed. Initial evaluation found subdural hematomas, persistent hypoxia, failure to thrive, a frenulum tear, facial lacerations, and bruising. The patient was admitted, and an extensive workup led to the diagnosis of brain and pulmonary arteriovenous malformations and finally the diagnosis of HHT. The subdural hematomas, cutaneous injuries, and oral injury were highly suspicious for child abuse and were reported to Child Protective Services and law enforcement for investigation simultaneous to the medical work-up. Her hospital course was complicated by progressive hypoxemia with radiographic evidence of several large pulmonary arteriovenous malformations, for which she underwent successful embolization. Her head injury was indeterminate for physical abuse in the setting of a medical condition predisposing to intracranial hemorrhage. A few weeks later, she was readmitted with repeat abusive injuries in the form of femur fractures. This case demonstrates the unique diagnostic dilemma when 2 diagnoses are occurring simultaneously-HHT and child abuse-and showcases the importance of a detailed family history, genetic testing, strong multidisciplinary collaboration with a holistic approach and medically informed Child Protective Services systems to ensure accurate diagnoses and safe disposition.